(untitled) (Indian Journal of Arid Horticulture, 2018)
Several local landraces of ridge gourd are spread over a wide range of environments in Rajasthan having specific traits. Evaluated 40 germplasm of ridge gourd under hot arid conditions of western Rajasthan over the years during summer season for different horticultural traits with special reference to high temperature tolerance. Among the evaluated germplasm, selected AHRG-29 (IC-0621468) for high temperature tolerance and purified through inbreeding and identified as variety ’Thar Karni’. Produced female flower on lower nodes (12.00-13.27) having 6.19-6.72 cm long ovary. It is early in harvesting and took 47.83- 50.00 days to produce 50% female flowering from sowing. Fruits are cylindrical, 20.19-22.45 cm long with 2.81-2.96 cm diameter weighing 90.18-102.36 g having 10 longitudinal shallow ridges. On an average a single plant produced 21.03 marketable fruits which are free from bitter principle. It showed tolerance to mosaic disease having 7.50% incidence and resistance against melon fruit fly with 17.67% fruit infestation under filed conditions. The plants of ’Thar Karni’ withstand to high temperature (upto 42 C) with moderate yield potential (151.87 q/ ha) which exhibited 31.44% higher yield over Arka Sujath and o37.56% over Pusa Nasdar (check).